Potential use of Floating Architecture for Flood Mitigation in Bulungan Regency - Sandhika, Rendy Rian; Maghzaya, Abdul Robbi (Journal of Architectural Research and Design Studies, 2024)
Flooding is a natural phenomenon in Bulungan that can affect the discomfort of people's living conditions. Floating house technology has the potential to be a flood mitigation strategy in Bulungan Regency, North Kalimantan. Through the study of Floating Architecture technology, including floating houses, raft houses with plastic drums and houses made of EPS (Expanded Polystyrene) material. This research explores the use of this technology in the context of flood mitigation in the Bulungan district. Analyzing various sources of information, this research identified 3 (three) potential technologies. This research is limited in being able to identify technologies that have the potential to be applied. Each of these technologies has similarities that have the potential to be applied as flood mitigation in Bulungan Regency, looking at aspects such as the Bulungan floating house concept, security and sustainability efforts. Keywords: Bulungan; floating house; flood house; flood mitigation; mitigation house